Antifungal activity against Alternaria solani and control of early blight in tomato by essential oil of citronella - Hendges, Camila; Stangarlin, José Renato; Zamban, Vanessa Cristina; Kuhn, Odair José; Lorenzetti Tartaro, Eloisa; Batista Carmelo, Donizete (Revista Ceres, 2023)
An alternative to the agrochemicals is the use of essential oils that can act in plant defense against phytopathogens. The objective of work was to evaluate the antifungal activity, the early blight control, and the enzymatic defense in tomato treated with citronella essential oil. Mycelial disks of the pathogen were added in Petri dishes, with treatments 0, 500, 1000, 1500, 2000 and 2500 μL L-1 of essential oil and a control treatment with fungicide, thus evaluated mycelial growth and sporulation. The treatments were applied in the second pair of leaves of plants (treated) and after 72 hours the pathogen was inoculated on the second pair (treated) and also on the third pair leaves (untreated). The severity was expressed through the area under the disease progress curve (AUDPC). The enzymatic activity of peroxidase, polyphenoloxidase, and phenylalanine ammonia-lyase were evaluated. The essential oil reduced the mycelial growth and sporulation of the pathogen. The AUDPC was reduced up to 38.14% in the treated leaves and 51.32% in the untreated, and increases in the activities of enzymes were found. The essential oil of citronella could be an alternative in the control of tomato early blight by antimicrobial activity and/or resistance induction local and systemically.